2019
DOI: 10.20849/ijsn.v4i3.588
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Barriers of Breast Self-Examination Among Women in a Rural Community in South Western, Nigeria

Abstract: Background: Breast cancer (BC) is the most common cancer and the second cause of cancer deaths in women worldwide as well as in Nigeria .The incidence of the disease appears to be rising faster in a population groups which had hitherto enjoyed low incidence, with the peak age of breast cancer in Nigerian women being about ten years earlier than Caucasians Aim: This study investigated the practice of BSE and its possible barriers among women in a rural community in South Western area of Oyo State; Nigeria.Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Another study carried out in Saudi Arabia revealed that only 18.7% of study subjects conducted BSE (Jahan et al, 2006). Similarly, Hanson et al (2019) noted that about half of their study subjects in a rural Community in South Western, Nigeria did not perform BSE. Some demographic characteristics importantly affect the practice of the BSE.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study carried out in Saudi Arabia revealed that only 18.7% of study subjects conducted BSE (Jahan et al, 2006). Similarly, Hanson et al (2019) noted that about half of their study subjects in a rural Community in South Western, Nigeria did not perform BSE. Some demographic characteristics importantly affect the practice of the BSE.…”
Section: Discussionmentioning
confidence: 95%
“…BSE is done autonomously by women, and it does not require any tools. About twenty percent of the time breast cancer is discovered by physical examination, thus it is recommended that all women perform BSE regularly as an important aspect of their breast cancer screening plan (Hanson et al, 2019). According to the American Cancer Society's guidelines for the early detection of breast cancer, women are advised to start annual breast cancer screening with mammography between the ages of 40 to 44 if they wish to do so (as a precautionary measure), and those aged 55 years or more should carry out mammography once every two years (Oeffinger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Five (5) out of the twelve (12) listed above added awareness to their findings (Tobin & Okeowo, 2014;Yakubu et al, 2014;Alabi et al, 2018;Ossai et al, 2019;Iwuoha et al, 2021). Three (3) (Ogun, 2019;Hanson et al, 2019) reported on knowledge, practice and perception while Sani and Yau (2018) reported knowledge and practice alone. Finally, Akpanekpo (2019), Olaogun et al (2017) and Madubogwu (2021) reported on awareness, attitude and practice.…”
Section: Study Findingsmentioning
confidence: 90%
“…All the articles reported a high rate of attitude towards BSE except Hanson et al (2019), Ogun (2019), Sani and Yau (2018) that did not give any report on attitude. Yakubu (2014), had a positive attitude.…”
Section: Attitude Toward Bsementioning
confidence: 99%
See 1 more Smart Citation